PENINGKATAN PEMBACAAN METROLOGI INDUSTRI PADA ALAT UKUR VIRNIER CALIPER DI SEKOLAH LANJUTAN TINGKAT ATAS - Minto; Muflihah, Nur; Mayasari, Andhika; Widya L, Jati; Basuki; N.F.A, Fatma Ayu; Sumarsono (ABIDUMASY, 2025)
Reading metrology tools, especially virnier calipers or vernier measuring tools, in the world of education, especially vocational schools, is still experiencing problems and only reads in mm (metric), not yet reading in inches. Some things institutions need to do are bring in technicians/practitioners or tutors to train students and teaching staff, but they are constrained by a large amount of funding. Finally, this obstacle was tried to be overcome by collaborating between SMK 10 November and the UNHASY Faculty of Engineering, especially industrial engineering. In industrial engineering, UNHASY also has industrial metrology equipment and professional technicians to carry out service activities entitled "Implementation of Industrial Metrology Readings Using Inches" . This training is very important and is needed by students to prepare for entering the world of work. And able to be competent in the world of work